Socio-aesthetic Engagement between Assemblies and Assemblages - Bondì, Antonino; De Luca , Valeria (E|C, 2024)
In this paper, we aim to address the issue of living together by focusing on two notions of engagement and social assemblage. Engagement describes an important phase in the tension between experience and value construction and sheds light on the ways in which agentivity, identity, and semiotic forms co-emerge. Starting from a pragmatist value formation theory, an ecological niche construction theory, and a material engagement theory, the article aims to show that engagement consists of a movement of perceptual and dialogical attention, oscillating between the pole of “active involvement” and the pole of “decision to participate”. In this sense, it offers a range of participatory options to social actors. We will then show that starting from this result, some forms of social assembly can be observed based on a specific mode of engagement: the assembly. To put our model to the test, we have traced an assembly-type collective formation in the field of “aesthetic communities”. Finally, we will discuss by analyzing the artistic experiment Lumbung, presented at Documenta 15 in 2022 by the Indonesian collective Ruangrupa, whose goal is the formation of communities in terms of assembling heterogeneity and engagement, which modulates the modal continuum of individuals’ participation in collectives.